Pengaruh Gaya Hidup, Kualitas Layanan dan Promosi Terhadap Keputusan Konsumen dalam Menggunakan GoFood Pada Masa Pandemi Covid-19 di Kota Bandar Lampung - Essy Amelia Amanda; Dorothy Rouly Haratua Pandjaitan; Mudji Rachmat Ramelan (Pusdikra Publishing, 2023)
The Covid-19 pandemic in Indonesia has affected all aspects of life, including the lifestyle of Indonesian society. Changes in lifestyle can be seen from various activities that should be done outside the home, which now have to be done at home and people only go out if it is necessary. These changes have made people rely heavily on digital technology to continue their social and economic activities during the pandemic. Gojek is one of the online transportation service companies in Indonesia that has provided convenience for consumers to fulfill their needs and carry out their activities during the Covid-19 pandemic, one of which is its food delivery service, Go-Food. The increasing number of competitors targeting the same market segment has led consumers to face several choices in using food delivery services. This study aims to determine the influence of lifestyle, service quality, and promotion on consumer decisions in using GoFood during the Covid-19 pandemic in Bandar Lampung City. The research method used in this study is quantitative method. The population in this study is all consumers who purchased and used GoFood services during the Covid-19 pandemic in Bandar Lampung City. The sample size in this study is 100 respondents using purposive sampling technique. Data were collected using a validated and reliable questionnaire. Data analysis in this study used multiple linear regression analysis. The results of this study indicate that lifestyle, service quality, and promotion variables have a positive influence on the decision to purchase GoFood during the Covid-19 pandemic in Bandar Lampung City.